Cutaneous vascular response and its role in the efficacy of laser-based aesthetic procedures - Alyamani, Nawal; Albyali, Shatha; Alenezi, Ahmad; Alqahtani, Lyan; Alshehri, Salem; Al-Awn, Maram; Asiri, Asma; Aldagdoog, Hawra; Alsuwailem, Faisal; Aleid, Nouf; Alsudais, Reemana (International Journal Of Community Medicine And Public Health, 2026)
Laser-based aesthetic procedures rely heavily on the interaction between laser energy and the skin’s vascular system. The effectiveness of these treatments often depends on the ability to precisely target and modulate blood vessels without damaging surrounding tissue. Key to this process is selective photothermolysis, where laser wavelengths are absorbed by hemoglobin, leading to controlled thermal injury and vessel coagulation. The biological response that follows includes inflammatory signaling, thrombosis, and subsequent vascular remodeling, all of which contribute to clinical improvements in conditions like telangiectasia, port-wine stains, and facial erythema. The extent of vascular response is shaped by numerous variables such as vessel size, blood flow rate, depth, and the optical properties of the skin. Laser parameters including wavelength, pulse duration, and fluence must be carefully matched to these vessel characteristics to ensure effective treatment. In patients with darker skin tones, melanin competes with hemoglobin for light absorption, raising the risk of pigmentation issues. Protective measures like epidermal cooling and longer wavelengths help reduce adverse effects while maintaining efficacy. Treatment outcomes are also influenced by anatomical location, pre-existing vascular conditions, and patient-specific healing responses. Technological advancements, including dynamic cooling, pulse stacking, and multispectral lasers, have improved precision and safety. Monitoring vascular behavior during treatment allows for real-time adjustments, making procedures more adaptable to individual needs. Together, a deeper understanding of vascular mechanisms and improved device control continues to expand the potential of laser-based aesthetics, offering more consistent and personalized results across a wide range of skin types and vascular presentations.